Trabalho no Brasil e a reforma de 2017: a (in)eficiência da produção legislativa sob a óptica da análise econômica do direito - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
The gradual deconstruction of social rights, especially those related to the lack of protection of the working class, has been remarkable. This panorama seems to represent the performance of the logic of capital in the universe of work, through a globalized system also established in the Brazilian State. Following such logic, comes up the Law 13.467 / 2017, called Labor Reform, which concretizes the logic of the prevalence of what the parties negotiated over what is provided by law, now covered by a rule issued by the State itself, and defended as a model capable of providing the increase in the numbers of employability in the country and reduction of the mass of workers in conditions of informality. In order to understand, then, the process that led to the movement for the enactment of the law, it is necessary that we also glimpse the contours of the historical movement of the structures that guided the national industrialization and deindustrialization models and that, finally, resulted in the prevalence of the flexible capital accumulation model and wide openness to the neoliberal paradigm. It is imperative, therefore, in view of the perceived context, that the effects of this change on the indicators that it had proposed to change are analyzed, in this case, by means of an instrument granted by the Economic Analysis of Law, more specifically in the concept of efficiency polished by Kaldor -Hicks, through which will be detected the inability of the new standard to promote an improvement balance in the conditions previously noted. For this purpose, a descriptive exploratory research will be used, conducted by the deductive method, proceeding to a qualitative analysis of the bibliographic and documentary sources, this corresponds to the legislation and socioeconomic data of the country within two years starting to be taken into account on the law's enactment date.
Keywords: Reforma trabalhista; Neoliberalismo; Industrialização; Análise econômica do direito; Eficiência; Labor Reform; Neoliberalism; Industrialization; Economic Analysis of Law; Efficiency; CNPQ::CIENCIAS SOCIAIS APLICADAS